“Two Pillars Of Sustainability”: Pemberdayaan Pendidikan Dan Lingkungan, Serta Pertumbuhan Ekonomi Daerah Melalui Perspektif Social Humanity - Deswari Ayu Putri; Reina Delvira; Aldiat Noverza; Rozi (Indonesian Journal of Dedication and Educations, 2023)
The humanitarian project in the 2023 of MBKM program is an activity concept designed to make "humanity" the main aspect in its implementation. Humanitarian projects implemented refer to the Sustainable Development Goals (SDG's) by prioritizing the development of two sustainable pillars that need to be supported in order to help the level of progress in achieving the SDG's, namely the economic and social pillars. In order to realize the objectives of this humanitarian project activity, it goes through several stages, namely preparation, implementation, monitoring and evaluation. The 16 (sixteen) programs that have been designed are implemented according to the schedule that has been agreed upon with partners to ensure that the activity concepts that have been prepared can be implemented well, which is then monitored and evaluated. The entire program is implemented well in accordance with the targets or target results. Which is aimed. This program is carried out with in-depth studies to create projects or several activities of a social nature involving all elements of society where the aim of this activity is to instill and foster a social and humanitarian spirit within students and society itself. This activity is a form of developing personal creativity for students to be able to spread benefits to the wider community. It is hoped that the existence of educational activities in the economic and educational sectors, as well as social activities related to environmental activities and so on, will be a step to increase the impact of other positive activities in the future.